Effective Use of Relaxation Training in Dealing With Tension and Anxiety: A Selected Review - Sherer, Shawn E.; Pass, Larry E. (Canadian Journal of Counselling and Psychotherapy, 2012)
Relaxation training is currently employed both in relation to systematic desensitization treatment of phobias and by itself as a direct means of dealing with tension and anxiety. A selected review of the literature suggests that the greatest benefit may be derived when the procedure is viewed as developing on active coping skill and directly related to the individual's daily living situation.